Sonic Hedgehog signaling in spinal cord injury: mechanisms and therapeutic implications - Du, Mingjuan; Ji, Xiaozhen; Chen, Weiting (Frontiers in Molecular Neuroscience, 2025)
Spinal cord injury is a serious neurological condition that results in severe dysfunction below the level of injury, often leading to long-term disability and impaired quality of life. Despite significant advances in medical care, effective treatment options remain limited. Recent research has highlighted the role of endogenous signaling pathways, including Sonic Hedgehog, in the natural healing response following SCI. Sonic Hedgehog (Shh) signaling pathway plays a vital role in spinal cord development and post-injury regeneration by regulating neuroprotection, axon regeneration, synaptic remodeling and inflammation. Shh exerts its effects through a well-defined cascade involving Patched (Ptch), Smoothened (Smo) and Gli transcription factors, ultimately influencing genes involved in neural repair. Various pharmacological agents including agonists (SAG, Purmorphamine and Shh-N) and antagonists (Cyclopamine, Vismodegib and Sonidegib) have been studied for their ability to modulate this pathway and enhance recovery in preclinical models. In addition, emerging approaches such as stem cell therapies, exosome delivery and nanotechnology-based drug targeting are under investigation to improve the efficacy and specificity of Shh-based treatments. However, despite promising experimental outcomes, the clinical translation of these findings faces significant challenges, including delivery limitations, potential tumorigenicity, immune variability and the lack of robust human data. This review critically examines the molecular mechanisms and therapeutic potential of Shh signaling in SCI, highlights current limitations and conflicting evidence and outlines future directions to bridge the gap between preclinical findings and clinical application.